Critical Illness, Gastrointestinal Complications, and Medication Therapy during Enteral Feeding in Critically Ill Adult Patients - Btaiche, Imad F. (2010)
Critically ill patients who are subjected to high stress or with severe injury can rapidly break down their body protein and energy stores. Unless adequate nutrition is provided, malnutrition and protein wasting may occur, which can negatively affect patient outcome. Enteral nutrition (EN) is the mainstay of nutrition support therapy in patients with a functional gastrointestinal (GI) tract who cannot take adequate oral nutrition. EN in critically ill patients provides the benefits of maintaining gut functionality, integrity, and immunity as well as decreasing infectious complications. However, the ability to provide timely and adequate EN to critically ill patients is often hindered by GI motility disorders and complications associated with EN. This paper reviews the GI complications and intolerances associated with EN in critically ill patients and provides recommendations for their prevention and treatment. It also addresses the role of commonly used medications in the intensive care unit and their impact on GI motility and EN delivery.